Configuration paths of community cafe to enhance residents’ well-being: fsQCA analysis of 20 cases in Shanghai - Zhang, Man; Shen, Tao; Lou, Yongqi (Frontiers in Public Health, 2023)
Community cafes have emerged as a critical infrastructure for promoting communication and cultural construction in urban areas, and have gradually become an essential public place to enhance residents' well-being. However, despite their growing importance, there is a dearth of empirical research on the emerging concept of community cafes, and a lack of configuration analysis of their influencing factors. To address this gap, this study employed the fuzzy set qualitative comparative analysis (fsQCA) method to examine 20 community cafes in Shanghai, China, and explore their configuration effects on residents' well-being across five dimensions: activity quality, psychological cognition, physical quality, physical accessibility, and sociability. The findings reveal that sociability is a necessary condition for high levels of resident well-being, and identify three configuration paths that generate high well-being. These paths can be classified into activity-based or acquaintance-based social interaction patterns according to the spatial functions. Additionally, the study identified five groups of non-high well-being configurations, in which lack of activity quality and sociability are core conditions. These findings contribute to the evaluation of community public spaces and provide insight into the configuration of factors that contribute to residents' well-being. The study highlights that community public spaces can have significantly different impacts on residents' well-being, with sociability emerging as a particularly important factor. Therefore, it is necessary to clarify community public space's social orientation according to spatial conditions.